Consumo energético de mulheres de baixa renda: comparação entre dois métodos de consumo alimentar, em relação à água duplamente marcada - Lins, Isabela Lays Lopes (2014)
Food consumption has gone through both qualitative and quantitative changes of ingested products, reflecting the increased prevalence of overweight and obesity. Epidemiological studies have increasingly emphasized the investigation of the association between dietary intake and development of obesity. However, the assessment of dietary intake is a complex task as it involves symbolic dimensions of social life and so this susceptible to errors. Thus, techniques for assessing the diet of individuals have been thoroughly reviewed. The doubly labeled water technique (ADM) can be used to validate methods for assessing the energy consumption. Thus, considering the increasing prevalence of obesity and chronic diseases in the population of northeastern Brazil, justifies the need for research to evaluate the accuracy of the methods to assess dietary intake used for this population. In this perspective the present study was developed with poor women living in slum Maceió- AL. Inclusion criteria were aged between 19 and 45 years old and being female. Pregnant women, diet therapy or with deformities that interfere with anthropometry were not included in the protocol. Socioeconomic, anthropometric, body composition and energy intake and expenditure profile were characterized. Dietary intake was assessed by three 24-hour recalls (24HR) , and a food frequency questionnaire . Energy expenditure was measured by doubly labeled water (ADM). Confidence intervals were calculated to define the breakpoints for sub -reporting and over-reporting. The results showed that the FFQ is closer to the GET obtained by ADM (p = 0.014). And there was a higher frequency of underreporting when rated the 24HR and ADM ( p = 0.09) . In conclusion, this study showed that the 24HR lower accuracy for evaluating food intake when compared to the FFQ method, compensation in the sub - accounts and super -reports were higher in the FFQ. Thus, both methods proved ineffective reviews to assess dietary intake in this population.